The use of polyurethane foams for the extraction of platinum (II) from hydrochloric acid solutions in the presence of tin (II) chloride - Brackenbury, Karim Francis Gavin (Department of Chemistry, 2016)
A preliminary investigation prior to the study of the extraction of platinum, was conducted on the Co(NCS)₄²⁻ /foam system to, (a) develop a suitable experimental apparatus in order to study the loading of platinum foams and (b) obtain fundamental kinetic and thermodynamic data concerning the sorption process. The sorption of platinum(II) as complexes of [Pt(SnCl₃)nCl₄-n]²⁻ and [Pt(SnCl₃)₅]³⁻ from hydrochloric acid solutions by polyurethane foams was examined in detail. Our studies show that the capacity of the foam to extract platinum depends on the following solution conditions of, temperature, initial platinum concentration, hydrochloric acid and hydrogen ion concentrations, the Sn:Pt ratio and the presence of interfering cations and anions. The rate of platinum sorption is shown to be dependent on temperature, initial platinum concentration, the Sn:Pt ratio and the mass of the foam. The foam's ability to selectively extract platinum from solutions containing platinum and certain base metals is examined. Results obtained show that in all cases almost complete extraction of platinum was achieved. Of all the base metals investigated only Cu(II) co-extracts to a small extent with the noble metal. In this work a procedure has been developed in which we are able to quantitatively recover both platinum and tin from loaded foams, by dissolving the polyurethane in warm nitric acid. A simple distillation allows for the satisfactory separation of platinum from tin.